Brook Rearrangement as a Trigger for the Ring Opening of Strained Carbocycles. Issue 2 (14th December 2015) - Zhang, Fa‐Guang; Eppe, Guillaume; Marek, Ilan
Abstract: The combined regio‐ and stereoselective carbometalation of cyclopropenyl amides, followed by the addition of an acyl silane, led to the formation of polysubstituted cyclopropyl derivatives as unique diastereoisomers. Upon warming of the reaction mixture to room temperature, a Brook rearrangement proceeded with inversion of configuration to provide ready access to δ‐ketoamides possessing a quaternary carbon center with high enantiomeric ratios through selective CC bond cleavage of the ring. Abstract : How many steps? One great stride : The regio‐ and stereoselective carbometalation of cyclopropenyl amides and addition of an acyl silane gave polysubstituted cyclopropyl derivatives, which underwent a Brook rearrangement with inversion of configuration and selective ring cleavage when the reaction mixture was warmed to room temperature. Hydrolysis then completed the one‐pot synthesis of δ‐ketoamides with a quaternary stereocenter (see scheme).